ANALISIS SISTEM E-FILING DAN E-SPT TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI KPP PRATAMA BATAM SELATAN - Rinni; Br. Purba, Neni Marlina (LPPM Universitas Putera Batam, 2022)
In generals, the term tax are no longer something foreign or rare heard by the people of Indonesia. In various mass media, let alone special media at the fields of economic, finances, and busines, we very often encounter or see or even read in the form of news, information or writing about taxes. The discrepancy in the number of registered and non-reporting taxpayers may be causing with much factoring. One of thems are in the use of e-filing and e-spt. This study aims for determining the effect of e-filing and e-SPT on individual taxpayers complianced at KPP Pratama Batam Selatan. That researches designed using researches designed and quantitatives researches method. Data’s collections technique with distribute questionnaire to 100 individual taxpayers at KPP Pratama Batam Selatan. That resulting of these studies indicated that E-filing (X1) and E-spt (X2) partials and simultaneous has a significants effected on Taxpayer Compliance (Y). The results of the coefficient of determinations test show that E-filing (X1) and E-spt (X2) affect Taxpayer Compliance (Y) by 52,1 percents, and 47,9 percent is influencing by others variables that not examined in these studies.